Sport mega-events and ‘terrorism’: A critical analysis - Giulianotti, Richard; Klauser, Francisco (My University, 2012)
The article explores critically the interplay between sport and terrorism, with particular reference to sport mega-events. Our discussion is divided into two main sections. First, we set out the main principles of a critical social theoretical approach, which enables satisfactory analysis of the ‘sport/terrorism’ couplet. We discuss the contribution of three types of critical perspective that are tied to different disciplines, namely sociology, human geography, and political science/international relations. Second, we turn to consider some of the main historical and contemporary incidents and issues with regard to terrorism at sport mega-events. On this basis, we show how and why social scientific analysis needs to move beyond common-sense understandings of the sport/terrorism couplet, to investigate critically the epistemologies and discursive constructions of terror, the logics, processes and relationships underpinning specific counter-terrorism strategies, and the wider socio-spatial implications thereof.
Keywords: cities; critical social theory; sport mega-events; terrorism